(untitled) (Al-Academy, 2019)
The space constitutes a cornerstone of the creativity process since the emergence of arts and literature. Gaston Bachelard has a significant role in highlighting the importance of the place in his book entitled (Poetics of Space). Since then, the space, especially in the TV drama, is no longer a mere background indicating the location or the date of the event. Space inside these series has become an inseparable part of the artistic or dramatic fabric, that the visual scene started to formulate alongside the movement of the individuals in their language or accents that are specified inside the space as an incubator for the décor, clothes, makeup, accessories and lights in addition to the sound and musical effects. The lens angles encounter the eyes of the creative photographer and creative director to create what can be called the visual unity. The series is, then, the process of the creative combination through the montage of a group of paintings or visual units. The research consists of two sections within the theoretical framework: The first section: space structure. It addressed space structure, dimensions and the way of employing it in the artistic work. The second section: the work mechanism of the dominating sign. It addressed the mechanisms of employment of the dominating sign of the space structure in the TV drama